Government Responsibility for The Fulfillment Basic Rights of Unprosperous people In Education Sector - Susanti, Pipi; Sari, Rafiqa (Susbtantive Justice International Journal of Law, 2021)
In fact, there are still many people living in poverty where they cannot fulfil their basic needs, be it food or clothing, there are still many children who drop out of school which causes ignorance. Education is one of the things that can change a family to be prosperous, therefore the government is obliged to fulfil this right. The problem in this paper is what form of government responsibility to fulfil the basic rights of the unprosperous people in education? The writing method used is normative with more emphasis on positive legal norms in the form of statutory regulations. The result of the discussion of this writing is that education is the basic right of the unprosperous people fulfilled by the government. In carrying out its responsibilities, the government fulfils the basic rights of the unprosperous people in several programs. Education which is the basic right of the unprosperous people is provided by the social service through PKH, while the Education Office provides these rights through (PIP) As stated in Article 31 of the 1945 Constitution, the community is required to get an education and the government is responsible for this, with some Indonesian program has fulfilled the rights of the unprosperous people in education.